2022
DOI: 10.3390/ijerph192013480
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Loads and Loading Position on the Muscle Activity of the Trunk and Lower Extremity during Squat Exercise

Abstract: This study aimed to investigate the effect of the load and bar position on trunk and lower extremity muscle activity during squat exercise. High bar back squats (HBBS) and low bar back squats (LBBS) were performed in random order at 50%, 60%, and 70% loads of one repetition maximum by 28 experienced healthy adult men who had been performing squats for at least one year. Before the experiment, the maximal voluntary contraction of the vastus medialis, vastus lateralis, rectus femoris, biceps femoris, rectus abdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…During the implementation of cardiopulmonary rehabilitation nursing, muscle strength evaluation should be added, and exercise training modes should be regularly adjusted through individualized nursing guidance to improve patients' flexibility in physical strength and functional adaptation parameters, thereby improving patients' cardiac function. Morucci (15) found that regular physical activity could regulate oxidative activity and cortisol levels, while cortisol levels are closely related to cardiac function in coronary heart disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…During the implementation of cardiopulmonary rehabilitation nursing, muscle strength evaluation should be added, and exercise training modes should be regularly adjusted through individualized nursing guidance to improve patients' flexibility in physical strength and functional adaptation parameters, thereby improving patients' cardiac function. Morucci (15) found that regular physical activity could regulate oxidative activity and cortisol levels, while cortisol levels are closely related to cardiac function in coronary heart disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were eligible participants to perform the curl-up protocol of this study. Exclusion criteria were subjects with a history of central or peripheral nerve lesions, abdominal and/or low back pain, medical rehabilitation, surgeries on the abdominal and/or spine, psychosomatic drugs, and psychiatric disorders [ 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…A more upright upper body or a greater trunk segment angle (TSA) afforded by a DFS (TSA: 63.6 ± 4,2; Figure 2, right) and a DHBBS (TSA: 46.3 ± 4,8; Figure 2, center) is associated with greater AKD than a low-bar back squat (LBBS-Figure 2, left), which has a more restricted relative to horizontal TSA of 40.7 ± 5.8 [16]. Moreover, a DHBBS allows for a greater degree of squatting depth than a LBBS because it permits more knee flexion, and this also impacts AKD (Figure 2) [38,47].…”
Section: Barbell Placement and Akdmentioning
confidence: 99%